Body mass index (BMI), waist circumference (WC) and obesity in the resident adults of Raipur District (Chhattisgarh state: India) - Singh, Varsha; Sahu, Meena; Yadav, Somnath; Harris, K K (Journal of Phytology, 2012)
Obesity is a medical condition characterized by accumulation of excess body fat leading to negative health consequences and reduced life expectancy. The latter could be attributed to various diseases, particularly cardiovascular diseases, diabetes mellitus type 2, obstructive sleep apnea, certain types of cancer and osteoarthritis. The present investigation was undertaken to evaluate obesity, appraised by BMI, in the Raipur District of Chhattisgarh State, India. A multiphase stratified random sampling method was performed on 688 adults of both sexes, with mean age 34yrs ± 16, from June to September 2011. Anthropometric measurements were recorded using standard instruments (weight scale and stadiometer). BMI was calculated using the statistical software SPSS version 20.0. The results divulged 19.91% of the adults to be overweight and 57% of them as obese. Amongst the male subjects, 23.55% and 7.97 %; and in case of females, 17.47% and 8.90 % were marked as overweight and obese respectively. As evident from the results, 8.5% were obese and another 20% are being overweight which could lead to future obesity, which is significantly associated with increased likelihoods of having depressive symptoms and an array of other cardiac diseases. Thus, lifestyle and mental health status could well be monitored and evaluated in the obese and overweight subjects in order to prevent the several disorders associated with obesity.